Bulbar and speech motor assessment in ALS: Challenges and future directions. Issue 7 (December 2013) - Green, Jordan R.; Yunusova, Yana; Kuruvilla, Mili S.; Wang, Jun; Pattee, Gary L.; Synhorst, Lori; Zinman, Lorne; Berry, James D.
Abstract: Bulbar motor deterioration due to amyotrophic lateral sclerosis (ALS) leads to the eventual impairment of speech and swallowing functions. Despite these devastating consequences, no standardized diagnostic procedure for assessing bulbar dysfunction in ALS exists and adequate objective markers of bulbar deterioration have not been identified. In this paper, we consider objective measures of speech motor function, which show promise for forming the basis of a comprehensive, quantitative bulbar motor assessment in ALS. These measures are based on the assessment of four speech subsystems: respiratory, phonatory, articulatory, and resonatory. The goal of this research is to design a non-invasive, comprehensive bulbar motor assessment instrument intended for early detection, monitoring of disease progression, and clinical trial application. Preliminary data from an ongoing study of bulbar motor decline are presented, which demonstrate the potential clinical efficacy of the speech subsystem approach.